Upregulation of Aquaporin 1 Mediates Increased Migration and Proliferation in Pulmonary Vascular Cells From the Rat SU5416/Hypoxia Model of Pulmonary Hypertension - Yun, Xin; Philip, Nicolas M.; Jiang, Haiyang; Smith, Zion; Huetsch, John C.; Damarla, Mahendra; Suresh, Karthik; Shimoda, Larissa A. (Frontiers in Physiology, 2021)
Pulmonary arterial hypertension (PAH) is a progressive disorder characterized by exuberant vascular remodeling leading to elevated pulmonary arterial pressure, maladaptive right ventricular remodeling and eventual death. The factors controlling pulmonary arterial smooth muscle (PASMC) and endothelial cell hyperplasia and migration, hallmark features of the vascular remodeling observed in PAH, remain poorly understood. We previously demonstrated that hypoxia upregulates the expression of aquaporin 1 (AQP1), a water channel, in pulmonary arterial smooth muscle cells, and that this upregulation was required for hypoxia-induced migration and proliferation. However, whether the same is true in a model of severe PAH and in pulmonary microvascular endothelial cells (MVECs), is unknown. In this study, we used the SU5416 plus hypoxia (SuHx) rat model of severe pulmonary hypertension, which mimics many of the features of human PAH, to determine whether AQP1 levels were altered in PASMCs and MVECs and contributed to a hyperproliferative/hypermigratory phenotype. Rats received a single injection of SU5416 (20 mg/kg) and then were placed in 10% O2 for 3 weeks, followed by a return to normoxic conditions for an additional 2 weeks. We found that AQP1 protein levels were increased in both PASMCs and MVECs from SuHx rats, even in the absence of sustained hypoxic exposure, and that in MVECs, the increase in protein expression was associated with upregulation of AQP1 mRNA levels. Silencing of AQP1 had no significant effect on PASMCs from control animals, but normalized enhanced migration and proliferation observed in cells from SuHx rats. Loss of AQP1 also reduced migration and proliferation in MVECs from SuHx rats. Finally, augmenting AQP1 levels in MVECs from control rats using forced expression was sufficient to increase migration and proliferation. These results demonstrate a key role for enhanced AQP1 expression in mediating abnormal migration and proliferation in pulmonary vascular cells from a rodent model that reflects many of the features of human PAH.